Development of Soviet Lithuania movie in 1947–1961 - Kaminskaitė, Lina (Genocidas ir rezistencija, 2009)
The archival documents related to the development of cinema in the Lithuanian SSR have not been extensively studied. There has been no comprehensive research into the specifics of the development of Lithuanian cinema in the Soviet era. However, such research is possible on the basis of the extensive documentation on the activities of the Ministry of Culture of the Lithuanian SSR, the Lithuanian Film Studios, and the Union of Cinematographers. The documents in the collections of these institutions include correspondence between Lithuanian institutions responsible for the development of cinema in the republic and the USSR’s central cinema management bodies, minutes of film review and evaluation, resolutions, orders of the USSR’s central cinema management bodies, etc.
Keywords: Soviet Lithuania; culture; cinema; censorship